33.4: Hybrid Phase Modulation for Low Crosstalk LCOS Based Wavelength Selective Switch. (26th August 2021) - Luo, Yuxiang; Pan, Yichen; Lu, Jiangang
Abstract : A hybrid phase modulation of liquid crystal on silicon (LCOS) was proposed to optimize the crosstalk and diffraction efficiency of the ports with different deflection angle of wavelength selective switch(WSS). With phase profile of high phase depth, the ports of small deflection angle may achieve high diffraction efficiency and low crosstalk. And the ports of large deflection angle may achieve low crosstalk and relative high diffraction efficiency with phase profile of low phase depth. The hybrid phase modulation shows the great potential application of multi‐port WSS.